Study of cobalt boride-derived electrocatalysts for overall water splitting. (22nd March 2018) - Chen, Zhengjun; Kang, Qing; Cao, Guoxuan; Xu, Ning; Dai, Hongbin; Wang, Ping
Abstract: The production of clean hydrogen fuel by the electrolysis of water requires highly active, low-cost and facilely prepared electrocatalyst that minimizes energy consumption. Here we report an active cobalt boride (CoB)-derived electrocatalyst for both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). The CoB catalyst can be readily deposed on 3D nickel foam (NF) using a simple electroless plating method. A comprehensive analysis of the CoB catalyst with scanning electron microscopy transmission (SEM), transmission electron microscopy (TEM), Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) techniques revealed that CoOOH is formed on the surface of CoB catalyst during the OER process and Co(OH)2 is formed in the HER process. The catalyst derived from CoB/NF exhibits low overpotentials towards both OER and HER in alkaline solution. The electrolysis cell using the CoB-derived catalyst couple requires a cell voltage of 1.69 V to afford a current density of 10 mA/cm 2, which compares favorably with most non-noble bifunctional electrocatalysts. The favorable combination of high-performance, low cost and facile preparation suggests that transition metal borides may act as promising electrocatalyst for water splitting. Graphical abstract: Cobalt boride can be deposed on nickel foam by a simple electroless plating method and the catalyst derived from CoB/NF exhibits favorable electrocatalytic activity towards both OER and HER. Highlights: CoB catalyst was deposited on nickel foam by a simple electroless plating method. CoB-derived electrocatalyst exhibits high activities towards OER and HER. The electrolysis cell using CoB-derived catalyst couple requires 1.69 V to afford a current density of 10 mA/cm 2 .